2020
DOI: 10.1016/j.jde.2019.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Existence of a weak solution to the fluid-structure interaction problem in 3D

Abstract: We study a nonlinear fluid-structure interaction problem in which the fluid is described by the three-dimensional incompressible Navier-Stokes equations, and the elastic structure is modeled by the nonlinear plate equation which includes a generalization of Kirchhoff, von Kármán and Berger plate models. The fluid and the structure are fully coupled via kinematic and dynamic boundary conditions. The existence of a weak solution is obtained by designing a hybrid approximation scheme that successfully deals with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 22 publications
(62 reference statements)
0
15
0
Order By: Relevance
“…They use Standard ⱪε, RNG ⱪ-ε as Turbulence Model. The consequences confirmed that the impact of distinctive turbulence fashions on the speed discipline is less, on the stress discipline is pretty large, and on the cost of the whole torque is a good deal large [4].…”
Section: Literature Reviewmentioning
confidence: 72%
“…They use Standard ⱪε, RNG ⱪ-ε as Turbulence Model. The consequences confirmed that the impact of distinctive turbulence fashions on the speed discipline is less, on the stress discipline is pretty large, and on the cost of the whole torque is a good deal large [4].…”
Section: Literature Reviewmentioning
confidence: 72%
“…However, most of the results concern the incompressible fluid case. The results on the existence of a weak solution typically deal with FSI problems where the elastic structure is described by a lower dimensional model of a plate/shell type, see [47,8,21,37,46,55] and references within. Exceptions are works [1,48] where the existence of a weak solution to FSI problems involving regularized, nonlinear, 3D viscoelastic structure and linear multilayered structure, respectively, were proven.…”
Section: Motivation and Literature Reviewmentioning
confidence: 99%
“…), readers are refer to e.g. [8,15,35,47] for weak solution results. Considering strong solutions, one can find related results in e.g.…”
Section: Introductionmentioning
confidence: 99%